EFFORTS TO IMPROVE TEACHER COMPETENCE IN UTILIZING CANVA DIGITAL MEDIA IN LEARNING THROUGH IHT AT SDN SYEKH TUBAGUS ABDULLAH, TASIKMALAYA CITY - caswita, caswita; Noviyani, Selvi (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2023)
Abstract: The problem in this research is the teacher's weakness in utilizing Canva-based learning media. Meanwhile, the aim of this research is to try to increase the teacher's competence in using Canva media for learning through In House Training (IHT). The research method used was a pre-experimental design with the type of one-group pre-test post-test design. It is said to be a pre-experimental design because this method is often referred to as